Multi-Year Pseudo-Persistence, Mobility, and Degradation of Glyphosate and Its Degradation Product (AMPA) in a Gleysol in Quebec (Canada) - Stéphane Petit; Marc Lucotte; Gilles Tremblay (Agriculture)
This study evaluates the pseudo-persistence of glyphosate over three growing seasons in agricultural soils (gleysol) in Québec, Canada. The experiment was carried out in long established plots following a corn–soybean–wheat rotation cycle with various combinations of N-fertilization (mineral N-fertilization, organic N-fertilization, without fertilization) and tillage techniques (conventional tillage and no-till). The periods between glyphosate applications were 250, 326, and 398 days. Soil sampling was carried out at 0–20 cm and 20–40 cm just before each new application of herbicide. Glyphosate was not detected in any sample. Its main degradation product, aminomethylphosphonic acid (AMPA), was found and quantified in approximately 50% of the samples. The detection frequency of AMPA was higher for conventional tillage compared to no-till. Levels ranged between 0.09 and 0.46 μg.g−1. The molar balance per hectare over the first 40 cm showed that the amount of glyphosate present in the form of AMPA in the soils sometimes exceeds the amount of glyphosate applied during the previous season (10.54 or 5.27 mol glyphosate.ha−1). The cumulative effect of glyphosate applications on AMPA levels over the 3 years, however, has not been demonstrated. The effect of conventional tillage on the persistence of AMPA is significant in 2 out of 3 years. The persistence of AMPA was higher for combinations of conventional tillage/mineral N-fertilization and conventional tillage/without fertilization practices. We suggest that conventional tillage can modify parameters related to soil structure or to the structural or functional composition of the bacterial community, which could impact the degradation and leaching of glyphosate and AMPA.